Prevalence and Predictors of Obstructive Coronary Artery Disease in Nonlow-risk Acute Chest Pain Patients Who Rule Out for Myocardial Infarction in the High-sensitivity Troponin Era. Issue 1 (5th June 2020) - Mahmoud, Osama; Beer, Dominik; Mahmaljy, Hadi; Youniss, Mohamed; Campoverde, Edwin Hernandez; Elias, Hadi; Stanton, Matthew; Patel, Maulin; Hashmi, Insia; Young, Katelyn; Kuppuraju, Rajesh; Jacobs, Steven; et al.
Abstract : Objectives: The best management approach for chest pain patients who rule out for myocardial infarction (MI) in the high-sensitivity troponin (hsTn) era remains elusive. Patients, especially those with nonlow clinical risk scores, are often referred for inpatient ischemic testing to uncover obstructive coronary artery disease (CAD). Whether the prevalence of obstructive CAD in this cohort is high enough to justify routine testing is not known. Methods: We conducted a retrospective cohort analysis of 1517 emergency department chest pain patients who ruled out for MI by virtue of a stable high-sensitivity troponin T (hsTnT) levels (defined as <5 ng/L intermeasurements increase) and were admitted for inpatient testing. Results: Abnormal ischemia evaluation (including 5.9% with evidence of fixed wall motion or perfusion defects) was 11.9%. Of those undergoing invasive angiography (n = 292), significant coronary stenoses (≥70% or unstable lesions) and multivessel CAD occurred in 16.8% and 5.5%, respectively. In a multivariate logistic regression model, known CAD, prior MI, chest pain character, mildly elevated hsTnT, and left ventricular ejection fraction <40% were predictive of an abnormal ischemia evaluation result, whereas electrocardiography findings and the modified History, EKG, Age, Risk factors, and troponin (HEART) score were not. Of note, 30-day adverse cardiac events were strikingly low at 0.4% with no deaths despite an overwhelming majority (>90%) of patients scoring intermediate or high on the modified HEART score. Conclusions: A considerable percentage of acute chest pain patients who rule out for MI by hsTn had evidence of obstructive CAD, and the modified HEART score was not predictive of an abnormal ischemia evaluation.